Diseño taller de mecánica diesel - sistema combinado con viguetas nervadas en 2 direcciones (2025)
This project responds to the need to guarantee the structural safety of an industrial building intended for Electrodiesel headquarters, located in Rodadero, designed considering the seismic requirements of the city of Santa Marta. This technical decision seeks to ensure an additional margin of safety against possible seismic events, considering the criticality of the equipment and operations housed in the structure. From an engineering point of view, the proposal promotes a resilient design adapted to higher seismic threat scenarios, while, at a social level, it represents a reliable infrastructure for the regional industrial sector. The central proposal consisted of the development of a combined structural system, consisting of reinforced concrete frames and structural walls, which efficiently resist gravity and seismic loads. The scope of the project ranged from seismic analysis to the dimensioning of foundations, vertical and horizontal elements, using computational tools such as ETABS and current technical standards (NSR-10). The design considered the use of square isolated footings with a slab depth of 1.3 m, calculated according to the bearing capacity of the soil and the loads transmitted by the columns. Among the main limitations, budget restrictions were identified, with an estimated cost between 250 and 300 million pesos, as well as environmental factors.